1978
DOI: 10.1620/tjem.124.177
|View full text |Cite
|
Sign up to set email alerts
|

Morphometrical analysis on topographical difference in size distribution, number and volume of islets in the human pancreas.

Abstract: Seven pancreases from nondiabetic autopsy cases were submitted to morphometrical analysis of the islets of Langerhans as a preliminary investigation of the diabetic pancreas.The pancreatic islets were approximately simulated by spheres of different sizes randomly dispersed in the three-dimensional space; thereon the parameters of Weibull function assumed for the distribution of islet radii were estimated stereologically from chord length measurements on histologic sec tions taken from different portions of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
1

Year Published

1978
1978
2010
2010

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 10 publications
4
43
1
Order By: Relevance
“…However, replication per se has not been evaluated in the present study. As expected (see Hellman 1959, Saito et al 1978, Hellerström et al 1988, islet cell mass was higher in the splenic portion of the pancreas in Wistar rats. This pattern of distribution was also present in hybrid and GK rats.…”
Section: Discussionsupporting
confidence: 87%
“…However, replication per se has not been evaluated in the present study. As expected (see Hellman 1959, Saito et al 1978, Hellerström et al 1988, islet cell mass was higher in the splenic portion of the pancreas in Wistar rats. This pattern of distribution was also present in hybrid and GK rats.…”
Section: Discussionsupporting
confidence: 87%
“…The tissue slices were cut perpendicular to the long axis of the pancreas at the tail 5 cm from the splenic end, a place considered most representative of pancreatic tissue on account of the relatively constant density of islets (Saito et al 1978). After fixation in 10% formalin, the slices were embedded in paraffin and a total of 770 serial sections 2,um thick were prepared from Case 1, 440 from Case 2 and 808 from Case 3.…”
Section: Methodsmentioning
confidence: 99%
“…In a study involving seven pancreases, the total number of islets varied between 3.6 and 14.8 million (19), and the total islet volume was 0.5 to 1.3 cm 3 . In that study all islets were included, and a large number of small islets dominated the reported value.…”
Section: The Number Of Islets In a Pancreas Revisitedmentioning
confidence: 99%